2020
DOI: 10.1177/2050640620905183
|View full text |Cite|
|
Sign up to set email alerts
|

Pancreatic cancer‐derived organoids – a disease modeling tool to predict drug response

Abstract: Background Organotypic cultures derived from pancreatic ductal adenocarcinoma (PDAC) termed pancreatic ductal cancer organoids (PDOs) recapitulate the primary cancer and can be derived from primary or metastatic biopsies. Although isolation and culture of patient-derived pancreatic organoids were established several years ago, pros and cons for individualized medicine have not been comprehensively investigated to date. Methods We conducted a feasibility study, systematically comparing head-to-head patient-deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 23 publications
2
56
0
6
Order By: Relevance
“…They subsequently received FOLFIRINOX treatment per clinical performance (figure 6A). ATM inhibition sensitised all PDOs to PAD as revealed by increased cell death ratio (CDR 44 ; figure 6B-C) and increased DNA damage (H2AX p-S139), but a lower proliferation (KI67) ( figure 6D). Interestingly, PDO#5 was the only sample that responded to PAD treatment in the absence of ATM inhibition ( figure 6C and E), although adding the latter still significantly increased cell death rate (figure 6C).…”
Section: Induced Hrdness In Relevant Preclinical Model Systemsmentioning
confidence: 99%
“…They subsequently received FOLFIRINOX treatment per clinical performance (figure 6A). ATM inhibition sensitised all PDOs to PAD as revealed by increased cell death ratio (CDR 44 ; figure 6B-C) and increased DNA damage (H2AX p-S139), but a lower proliferation (KI67) ( figure 6D). Interestingly, PDO#5 was the only sample that responded to PAD treatment in the absence of ATM inhibition ( figure 6C and E), although adding the latter still significantly increased cell death rate (figure 6C).…”
Section: Induced Hrdness In Relevant Preclinical Model Systemsmentioning
confidence: 99%
“…Frappart et al created a predictive platform for therapeutic agents based on pancreatic ductal adenocarcinoma organoids. Two analyses were used to assess the effect of drugs, which included measuring the cell death ratio and calculating the area under the curve [ 118 ]. An interesting study by Sharick et al used optical metabolic imaging to assess the metabolic response of breast and pancreatic tumor patient-derived organoids in drug screening [ 119 ].…”
Section: Spheroids and Organoids For Personalized Medicinementioning
confidence: 99%
“…These results are supported by studies of lung cancer that have indicated a tight interconnection between these two genes [17,34,94]. However, to further determine the regulatory consequences and to investigate the biological and therapeutic relevance of LINC00261 for PDAC growth, invasion, or metastasis, one should consider additional model systems, such as organoids [95][96][97] or mouse models [98,99].…”
Section: Discussionmentioning
confidence: 83%